(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
The global food sector is evolving greatly towards sustainability. This is primarily because more and more individuals are growing aware of environmental problems. Nonetheless, there is a scarcity of studies concentrating on green restaurants among consumers in Malaysia. To fill this gap, our study tries to clarify the elements influencing consumers’ intentions to return to green restaurants. Using a survey method with purposive sampling, data on consumers’ intentions to revisit green restaurants were collected. The study adopted a model based on the Value-Belief-Norm (VBN) theory and analysed survey data from 249 adults using SmartPLS version 4.1.1.4. The results indicate that green consumerism along with product pricing contributed to consumers’ intentions to return to green restaurant. Conversely, perceived value and quality did not demonstrate a significant impact on revisit intention. These insights hold valuable implications for green restaurant managers and policymakers who are seeking to foster sustainability within the food service sector. Furthermore, the findings contribute to the advancement of theoretical understanding, offering an extension to the VBN theory.